Global Exponential Stability in Lagrange Sense for Delayed Memristive Neural Networks with Parameter Uncertainties (Journal of Nonlinear Modeling and Analysis, 2024)
This paper addresses the Lagrange stability of memristive neural networks with leakage delay and time-varying transmission delays as well as parameter uncertainties. Based on the theory of Filippov's solution, by using Lyapunov-Krasovskii functionals and the free-weighting matrix method, sufficient conditions in terms of linear matrix inequality (LMI) are given to ascertain the networks with different kinds of activation functions to be stable in Lagrange sense. Meanwhile the estimation of globally attractive sets is given. Finally, numerical simulations are carried out to illustrate the effectiveness of theoretical results.
Keywords: Memristive neural networks; Lagrange stability; Leakage delay; Uncertain parameters.